QSAR, ADMET, and Molecular Docking of Pyrazole Carboxamide Derivatives as Potential Antifungals Against the Fungus Rhizoctonia solani - Aziz, Hafiz Aji; Sari, Adani Ghina Puspita; Al-Ghani, Ranggaweny; Novianti, Tria Nurwina (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2024)
Sheath blight is generally caused by the fungus R. solani. The emergence of this fungus causes losses for farmers due to reduction of grain crops (cerelia) production such as rice. Thus, the use of antifungal compounds containing succinate dehydrogenase inhibitors is an effort to control sheath blight of the fungus R. solani. This research examines a new pyrazole carboxamide derivative designed as a succinate dehydrogenase inhibitor. Antifungal activity value prediction was determined using the Quantitative Structure-Activity Relationship (QSAR) equation and visualization of the interaction of pyrazole carboxamide derivatives with succinate dehydrogenase inhibitors was determined using molecular docking. A total of 29 pyrazole carboxamide derivatives and activities (EC50) were used in this study for QSAR modelling and molecular docking. The structure was optimized using the DFT/B3LYP/LanL2DZ method as an electronic descriptor calculation and QSAR modelling using the Multiple Linear Regression (MLR) method. The MLR test shows a valid QSAR equation model with good modelling accuracy and produces an equation logEC50 = 2.3936( 0.9447)[C13] + 9.1367 ( 3.0682)[C10] + 2.2473( 0.6055)[HOMO] - 48.1289( 14.1289)[C4] + 1.3937( 0.9465)[C14] + 28.3750( 6.6731) with R2tr = 0.8911; Q2 = 0.793; F = 28.079; R2val = 0.9908; and RMSE = 0.3450. ADMET analysis using ADMETlab indicated that the new pyrazole carboxamide derivative complies with Lipinski's rules, is moderately carcinogenic, and includes inhibiting the activity of hERG blockers. The new pyrazole carboxamide derivatives that have potential as succinate dehydrogenase inhibitors were determined based on the interaction of the docking results, namely compound A1, A5, and A7 -4.9, -5.1, and -5.3 kcal/mol, respectively.